From Turbine to Wind Farms Technical Requirements and Spin-Off Products - Krause, Gesche (IntechOpen, 2011)
This book is a timely compilation of the different aspects of wind energy power systems. It combines several scientific disciplines to cover the multi-dimensional aspects of this yet young emerging research field. It brings together findings from natural and social science and especially from the extensive field of numerical modelling.